Activity and diffusivity of oxygen in the liquid dilute BixSb1-x solutions - Jendrzejczyk-Handzlik D.; Handzlik P.; Fitzner K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The diffusivity and activity coefficient of oxygen in liquid antimony, bismuth and antimony-bismuth alloys were determined from coulometric titration experiments, which were performed in the temperature range from 985 to 1185 K. The diffusivity in pure metals (in cm2/s) is: Dbi,O =(9.04 ± 1.82)∙10-3 exp (-49115±1809/RT) DSb,O(2.87±0.22)∙10-4 exp (-16720±677/RT). The standard free energy of solution of oxygen in liquid antimony, bismuth and antimony-bismuth alloys according to the reaction ½ O2 (g) = O (infinite dilution) is calculated. The activity coefficient of oxygen was calculated at 1085 K as a function of the alloy composition. It was demonstrated that Wagner's model with one adjustable parameter h gave a satisfactory description of the experimental data.